2020
DOI: 10.1177/0021998320906007
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical and physical properties of nylon 6/glass fiber-reinforced hybrid composites manufactured by thermal and ultraviolet-cured pultrusion methods

Abstract: In this study, the effect of hybridizing glass fiber-reinforced polymer composites with nylon 6 fibers on the physical and mechanical properties of composites was investigated experimentally. The ultraviolet-cured and thermal pultrusion methods were employed for manufacturing the glass fiber-reinforced polymer and hybrid composite rods containing different volume percentages of nylon 6 fibers at low and high temperatures. The effects of the nylon 6 fibers and the pultrusion methods were investigated on the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The results showed that optimum processing conditions, which give the highest flexural strengths in the flow direction, correlate with the existence of a longitudinal and transverse gradient of fiber content, a high average length of fibers and a layered structure. The results reported by Teixeira et al 6 for materials were similar to those in the study by Lafranche et al 3 Alikhani et al 10 studied the physical and mechanical properties of nylon 6/glass fiber hybrid composites, manufactured by ultraviolet-cured pultrusion (maximum temperature of 48°C with UV LED lamps, in order to preserve the properties of nylon 6 fibers) or by the thermal pultrusion process (use of electric heating elements that provide a uniform temperature of 150°C). In both the processes, the presence of the nylon 6 fibers gives rise to a longer curing time, but with the UV-cured process, the composites were cured within 8 s against more than 10 times with the thermal process.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The results showed that optimum processing conditions, which give the highest flexural strengths in the flow direction, correlate with the existence of a longitudinal and transverse gradient of fiber content, a high average length of fibers and a layered structure. The results reported by Teixeira et al 6 for materials were similar to those in the study by Lafranche et al 3 Alikhani et al 10 studied the physical and mechanical properties of nylon 6/glass fiber hybrid composites, manufactured by ultraviolet-cured pultrusion (maximum temperature of 48°C with UV LED lamps, in order to preserve the properties of nylon 6 fibers) or by the thermal pultrusion process (use of electric heating elements that provide a uniform temperature of 150°C). In both the processes, the presence of the nylon 6 fibers gives rise to a longer curing time, but with the UV-cured process, the composites were cured within 8 s against more than 10 times with the thermal process.…”
Section: Introductionsupporting
confidence: 62%
“…[1][2][3][4][5][6] These materials that combine low density and high mechanical properties can be produced by controlled processes like thermocompression (organosheet), stamping/overmolding, or tape placement. [7][8][9] Moreover, their disposal for recycling [10][11][12][13][14] is a major advantage in many industrial areas, especially in the automobile sector in which fuel consumption and pollutant emission are directly related to vehicle weight. Two ways are currently being explored for the implementation of semi-structural or structural parts by melt impregnation: (a) the reactive route in which the polymer is formed in situ by reactions of liquid monomeric or oligomeric precursors; (b) the non-reactive (polymer) route in which the polymer is directly introduced into the mold.…”
Section: Introductionmentioning
confidence: 99%
“…A data logger system consisting Electronic Control Panel and Computer is used for recording the readings. As shown in figures 4(a) and (b), the test specimens were prepared as per ASTM D638 for tensile testing and ASTM D790 for flexural testing [26]. Tensile testing of the test piece provides an indication of the specimen's resistance to permanent deformation, whereas flexural testing indicates the specimen's resistance to deformation due to bending stress.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…11). A relatively low peak temperature that is typically reached during UV-cured pultrusion makes it possible to use temperature-sensitive reinforcements such as Nylon6 [78]. Another route is microwave-assisted pultrusion.…”
Section: Alternative Curing/heating Technologiesmentioning
confidence: 99%